Pilot implementation of two specific problem lists before and after solid organ transplantation into routine care - Higgen, Sanna; Müller, Evamaria; Barten, Markus J.; Eickhoff, Doreen; Grahammer, Florian; Härter, Martin; Bart, Sabine; Sterneck, Martina R.; Buchholz, Angela (Frontiers in Psychology, 2025)
IntroductionPsychosocial distress and mental health problems are common in patients before and after solid organ transplantation and can negatively affect morbidity, mortality, and adherence. Even though regular screening is recommended to identify patients with high levels of distress, the implementation in routine care has been insufficient so far.MethodsTwo newly developed problem lists for patients before and after transplantations were pilot implemented for 8 weeks at the Medical Center Hamburg Eppendorf (UKE) to identify factors facilitating and impeding their implementation.ResultsHealth care professionals evaluated its appropriateness, feasibility, and the cooperation with the psychologists before (HCPs: n = 23) and after (HCPs: n = 19) the implementation. Four psychologists assessed the appropriateness and feasibility by answering to open-ended and close-ended questions. Additionally, patients before (n = 8) and after (n = 100) transplantation filled out the screening and rated its acceptance. Only the data of the patients after transplantation were analyzed due to the small sample size of patients before transplantation. HCPs and psychologists rated the screenings as very appropriate [HCPs: M = 3.84 (SD = 0.77) to M = 4.32 (SD = 0.58)]. It was also highly accepted among patients [M = 4.23 (SD = 0.85) to M = 4.68 (SD = 0.65)]. Contentment with the psychological support and understanding of the mental health problems among HCPs increased significantly from before to after the implementation (U = 107.50, p < 0.05, r = 0.33; U = 107.00, p < 0.05, r = 0.34). The feasibility of the problem list post-Tx in routine care, however, was seen as challenging [HCPs: M = 3.11 (SD = 1.05) to M = 3.47 (SD = 1.07)].DiscussionThe distress screening was accepted and improved the cooperation between different professions. Barriers to implementation can be lack of staff and resources. Future studies should assess the adoption and sustainability of the screening in routine care.